Empowering to Reduce Intentions to Resist Future Change: Organization‐Based Self‐esteem as a Boundary Condition. (5th October 2020) - Neves, Pedro; Pires, Daniela; Costa, Sandra
Abstract: Research examining resistance to change usually focuses on what happens during (or immediately prior to) implementation. However, researchers also acknowledge that organizational life, including change events, do not occur in a vacuum and that individuals form intentions to resist future change based on their prior experiences. Building on uncertainty reduction theory, we examined the role of empowering leadership in the reduction of intentions to resist future change. Using a time‐lagged design, we found that empowering leadership reduces behavioural intentions to resist future change via structural empowerment. The indirect effect on cognitive and affective intentions was significant only for high organization‐based self‐esteem (OBSE) individuals. We also found a positive effect on cognitive intentions via psychological empowerment, again only for high OBSE individuals. These findings suggest that, to anticipate and prevent potential resistance to change, organizations should take a long‐term approach to change management, namely by stimulating empowering leadership during times of stability.